Effect of Process Variables on the Development and Characterization of Nanocellulose as Novel Biopolymer - Keshavamurthysetty, Pradeep Heregangur; Patel, Dipti Hiteshkumar (Indian Journal of Pharmaceutical Education and Research, 2023)
Nanocellulose has excellent mechanical, physical, and biological properties; it is an ideal material for many applications. The present study aimed to develop nanocellulose from cellulose by hydrolyzing with sulphuric acid to yield nanocellulose. In order to prepare nanocellulose, two factors were considered: the concentration of sulphuric acid and the variation in temperature (AHNC1 to AHNC5). Optimized NC was characterized by its size, zeta potential, TEM, XRD, and FT-IR. NCs had a size range between 134 to 644 nm. AHNC4 and AHNC5 showed respective Zeta potentials of -40.6 and -37.4. XRD diffractograms showed crystallinity indices in the 55-66% range. The TEM showed that the nanocellulose was semicrystalline. FT-IR measurement showed a peak at 1177 cm-1 due to O-H association bond of nanocellulose, which is similar to cellulose's peak. This work analyzed that the nanocellulose preparation involves the optimization process to get the desired size of particles by altering process parameters in the acid hydrolysis method like concentration of acid and temperature maintained during the reaction, which depend on the source of cellulose used in the development of nanocellulose.
Keywords: Nanocellulose; Acid hydrolysis; CNC; CNF; Nanocrystals